Non-immune system comorbidity in neuromyelitis optica spectrum disorders. (January 2023) - Cai, Linjun; Chen, Hongxi; Shi, Ziyan; Wang, Xiaofei; Du, Qin; Zhang, Ying; Lang, Yanling; Kong, Lingyao; Luo, Wenqin; Mou, Zichao; Lin, Xue; Zhou, Hongyu
Highlights: Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune inflammatory disease of the central nervous system (CNS) characterized by optic neuritis and transverse myelitis. Several previous studies have shown that multiple sclerosis (MS) comorbidities are related to clinical characteristics and disability, but there is a little article about NMOSD comorbidities. Therefore, this study investigated the relationship between NMOSD comorbidities and clinical characteristics, treatment response, and prognosis of the disease. Our study provides assistance for clinical practice management. Abstract: Comorbidities may influence the clinical features, prognosis, and treatment outcomes of neuromyelitis optica spectrum disorders (NMOSD). The aim of this study was to determine the status of non-immune system comorbidities in patients with NMOSD and the effect on treatment response and prognosis. We retrospectively collected data from all patients who met the 2015 NMOSD diagnostic criteria from the NMOSD database established by our center. Patients were divided into positive and negative groups based on the presence of non-immune disease comorbidities. Patient data, clinical characteristics, treatment response, prognosis, and mortality were compared between the two groups. A total of 138 patients with NMOSD plus comorbidities were included, and 404 patients without comorbidities were selected as controls. The average age at onset was older (45 years vs 38 years, P < 0.001), the mean body mass index was higher (23.12 vs 22.04, P = 0.042) and more patients experienced relapse after immunotherapy (68.5 % vs 54.5 %, P = 0.020) in the comorbidity group than in the non-comorbidity group. Multifocal central nervous system lesions as an initial symptom was more common in the comorbidity group than in the non-comorbidity group (30.4 % vs 18.32 %, P = 0.003). Further, more patients experienced severe vision attacks (28.3 % vs 15.8 %, P = 0.003) and severe motor attacks (30.4 % vs 11.9 %, P < 0.001) in the comorbidity group than in the non-comorbidity group. In conclusion, patients with NMOSD with comorbidities tended to be older, less responsive to treatment, and at a higher risk of vision loss and paralysis.